Method for testing porosity of high-purity quartz coating

The sample blocks are made by high-purity quartz slurry and their physical parameters are measured, and the porosity is calculated in combination with the standard method after high-temperature sintering. The problem of cumbersome and time-consuming detection in the existing technology is solved, and efficient and accurate porosity testing is achieved.

CN119198480APending Publication Date: 2024-12-27GCL PV MATERIALS XUZHOU CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411318849.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-21
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The porosity detection method for the high-purity quartz coating in the prior art is cumbersome and time-consuming, resulting in waste of energy and difficult operation, making it impossible to directly detect the porosity.

Method used

High-purity quartz slurry is prepared by mixing high-purity quartz sand and pure water. Samples are made through molds, and the weight, diameter and thickness of the sample are measured, and the volume of solid matter and pore volume are calculated. After high-temperature sintering, they are calculated according to the standard method. Porosity, the accuracy of the test results is verified by comparing the two methods.

Benefits of technology

The test process is optimized, the operation difficulty is reduced, the energy waste is reduced, the efficiency and sustainability of porosity tests are improved, and the accuracy of the test results is ensured through deviation value verification.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119198480A_ABST
    Figure CN119198480A_ABST
Patent Text Reader

Abstract

The invention discloses a high-purity quartz coating porosity testing method, which comprises: 1, selecting high-purity quartz sand and pure water, grinding the high-purity quartz sand, and mixing the ground high-purity quartz sand with the pure water to obtain a high-purity quartz slurry; 2, cutting a crucible block on the crucible body, and manufacturing a mold base; and step 3, supplementing water to the surface of the mold base by adopting a high-purity brushing method, brushing high-purity quartz slurry on the side wall of the mold base, enabling the high-purity quartz slurry to be solidified on the side wall of the mold base, and testing whether the high-purity quartz slurry meets the requirements of a high-purity quartz coating or not. According to the method for testing the porosity of the high-purity quartz coating, the testing process can be optimized, the difficulty of testing operation can be reduced, the situation that the porosity of the sample block can be tested only after the sample block is sintered according to a standard testing method is avoided, energy waste is reduced, time and labor are saved, and the testing efficiency and sustainability of the porosity of the coating are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of quartz coating porosity detection, and in particular to a method for testing the porosity of a high-purity quartz coating. Background Art

[0002] High-purity quartz coating is a delicate and efficient protective barrier. It is made of extremely high-purity quartz material, has excellent chemical stability and excellent high-temperature resistance, can effectively isolate impurities and pollutants in the external environment, and ensure that the coated object can still maintain excellent purity and chemical stability under extreme conditions (such as high temperature environment), and prevent metal impurities on the inner wall of the crucible from penetrating into the silicon melt and the final silicon ingot. It not only reduces the scope of the red zone at the edge of the silicon ingot, but also greatly guarantees the purity of the molten silicon and the subsequent solidification process, thereby comprehensively improving the overall quality and performance of the silicon ingot. The higher the density of the high-purity quartz coating, the stronger the barrier effect on impurity diffusion.

[0003] However, since the coating thickness and porosity are two important indicators for evaluating the compactness of the coating, and the coating thickness can be directly measured by a vernier caliper, the coating porosity cannot be directly detected, and the coating sample needs to be sintered at 1135 degrees for 3 hours, and the measured porosity can be obtained according to the standard GB / T 2997-2015 dense shaped refractory product volume density, apparent porosity and true porosity test method, but the use of this method to test the porosity of the coating is not only complicated and difficult, but also requires a lot of time to sinter the sample, resulting in a waste of energy. Therefore, those skilled in the art provide a method for testing the porosity of a high-purity quartz coating to solve the problems raised in the above background technology. Summary of the invention

[0004] The purpose of the present invention is to provide a method for testing the porosity of a high-purity quartz coating to solve the problems raised in the above background technology.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] A method for testing the porosity of a high-purity quartz coating, the method comprising the following steps:

[0007] Step 1: Select high-purity quartz sand and pure water, grind the high-purity quartz sand, and mix the grinded high-purity quartz sand with pure water to obtain high-purity quartz slurry;

[0008] Step 2: Cut a crucible block from the crucible body to make a mold base;

[0009] Step 3: Use a high-purity brushing method to replenish water on the surface of the mold base, and brush high-purity quartz slurry on the side wall of the mold base, let the high-purity quartz slurry solidify on the side wall of the mold base, and test whether the high-purity quartz slurry meets the requirements of high-purity quartz coating;

[0010] Step 4: placing the shaping mold on the end face of the mold base, pouring high-purity quartz slurry into the mold cavity of the shaping mold, allowing the high-purity quartz slurry to stand, allowing the high-purity quartz slurry to solidify, and demolding the solidified quartz slurry sample to obtain a primary embryo sample;

[0011] Step 5: Place the pre-embedded sample block in an oven for drying to obtain a finished sample block;

[0012] Step 6, measuring the weight, diameter and thickness of the finished sample obtained in step 5, calculating the solid matter volume and pore volume of the finished sample according to the weight, diameter and thickness of the finished sample, and substituting the solid matter volume and pore volume of the finished sample into the porosity calculation formula to calculate the porosity 1 of the finished sample;

[0013] Step 7: high temperature sintering the finished sample obtained in step 5 to obtain a final sample, and calculating the porosity of the final sample according to the standard GB / T2997-2015 dense shaped refractory product bulk density, apparent porosity and true porosity test method to obtain a porosity of 2;

[0014] Step 8: Compare the porosity 1 obtained in step 6 with the porosity 2 obtained in step 7 to obtain the deviation value of the porosity 1 and the porosity 2. According to the deviation value of the porosity 1 and the porosity 2, verify whether the porosity test method is feasible and confirm that the porosity test result is accurate.

[0015] The porosity calculation steps of the finished sample in step 6 are as follows:

[0016] (1)

[0017] (2) V a =V b -V t

[0018] (3)

[0019] (4)

[0020] Substituting formula (1), (2) and (3) into formula (4) yields the calculation formula for the porosity of the finished sample:

[0021] (5)

[0022] Where π a is the porosity of the finished sample, Vb is the total volume of the finished sample, V a is the pore volume, V t is the volume of solid matter, the total volume of the finished sample V b V is the volume of the solid substance t and pore volume V a The sum of , D is the sample diameter / cm, t is the sample thickness / cm, m is the sample mass, ρ t is the true density of quartz g / cm 3 .

[0023] Preferably, the grinding and mixing equipment for the high-purity quartz sand in step one is a ball mill, and the ball milling time is 12-15 hours.

[0024] Preferably, the water content of the high-purity quartz slurry in step 1 is 20%-40%.

[0025] Preferably, the shaping mold in step 4 is a silicone mold, and the shape of the mold cavity in the silicone mold is circular.

[0026] Preferably, in step 2, the end surface area of ​​the mold base is larger than the area of ​​the shaping mold.

[0027] Preferably, the standing time of the high-purity quartz slurry in step 4 is 1-3 hours.

[0028] Preferably, the drying temperature of the primary embryo sample in step 5 is 105-115°, and the drying time is 2-3h.

[0029] Preferably, the weight, diameter and thickness of the finished product sample in step six are measured using an electronic scale or a vernier caliper.

[0030] Preferably, the deviation value range of porosity 1 and porosity 2 in step eight is 0-5%.

[0031] Preferably, the sintering temperature of the finished sample in step seven is 1100-1200°, and the sintering time is 2-4h.

[0032] Compared with the prior art, the advantages of the present invention are: the test method for the porosity of the high-purity quartz coating proposed in the present application can use the same high-purity quartz slurry as the high-purity quartz coating to make a sample block, and measure the weight, diameter and thickness of the sample block, and calculate the solid matter volume and pore volume of the finished sample block according to the weight, diameter and thickness of the sample block, and then calculate the porosity of the sample block according to the solid matter volume and pore volume of the sample block, so as to know the porosity of the high-purity quartz coating, optimize the test process, reduce the difficulty of the test operation, avoid the situation that the sample block needs to be sintered according to the standard test method before the porosity of the sample block can be tested, reduce energy waste, save time and labor, and improve the test efficiency and sustainability of the coating porosity. In addition, in order to ensure the accuracy of the test results, by following the standard GB / T 2997-2015 Test method for bulk density, apparent porosity and true porosity of dense shaped refractory products is to sinter the specimens and calculate the porosity of the sintered specimens. The two porosities are compared before and after sintering to obtain the deviation between the two porosities. The feasibility of this test method is verified based on the deviation value and deviation range between the porosities calculated by the two methods, thereby confirming that the porosity test results are accurate and ensuring the accuracy of the test results. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 The figure is a flowchart of a method for testing the porosity of a high-purity quartz coating according to an embodiment of the present invention. DETAILED DESCRIPTION

[0034] In the description of the present invention, it should be understood that the terms "center", "lateral", "up", "down", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside" and the like indicate positions or positional relationships based on the positions or positional relationships shown in the accompanying drawings, which are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the present invention. In addition, the terms "first" and "second" are used only for descriptive purposes, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Thus, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, unless otherwise specified, "multiple" means two or more. In addition, the term "including" and any variation thereof are intended to cover non-exclusive inclusions.

[0035] Overall implementation plan:

[0036] Combination Figure 1As shown, a method for testing the porosity of a high-purity quartz coating comprises the following steps: step 1, selecting high-purity quartz sand and pure water, grinding the high-purity quartz sand, and mixing the ground high-purity quartz sand with pure water to obtain a high-purity quartz slurry; step 2, cutting a crucible block from a crucible body to make a mold base; step 3, using a high-purity brushing method to replenish water on the surface of the mold base, and brushing the high-purity quartz slurry on the side wall of the mold base, allowing the high-purity quartz slurry to solidify on the side wall of the mold base, and testing whether the high-purity quartz slurry meets the requirements of the high-purity quartz coating; step 4, placing a shaping mold on the end face of the mold base, and pouring the high-purity quartz slurry on the shaping mold. The mold cavity of the mold is placed, and the high-purity quartz slurry is allowed to stand, and the high-purity quartz slurry is allowed to solidify, and the solidified quartz slurry sample is demoulded to obtain a preliminary sample; step five, the preliminary sample is placed in an oven for drying to obtain a finished sample; step six, the weight, diameter and thickness of the finished sample obtained in step five are measured, and the solid matter volume and pore volume of the finished sample are calculated according to the weight, diameter and thickness of the finished sample, and the solid matter volume and pore volume of the finished sample are brought into the porosity calculation formula to calculate the porosity of the finished sample 1; step seven, the finished sample obtained in step five is sintered at high temperature to obtain a final sample, and according to the standard GB / T 2997-2015 Test method for bulk density, apparent porosity and true porosity of dense shaped refractory products Calculate the porosity of the final sample to obtain porosity 2; Step 8, compare the porosity 1 obtained in step 6 with the porosity 2 obtained in step 7 to obtain the deviation value of porosity 1 and porosity 2. According to the deviation value of porosity 1 and porosity 2, verify whether the porosity test method is feasible and confirm that the porosity test result is accurate; The porosity calculation steps of the finished sample in step 6 are as follows:

[0037] (1)

[0038] (2) V a =V b -V t

[0039] (3)

[0040] (4)

[0041] Substituting formula (1), (2) and (3) into formula (4) yields the calculation formula for the porosity of the finished sample:

[0042] (5)

[0043] Where π a is the porosity of the finished sample, V b is the total volume of the finished sample, V a is the pore volume, V tis the volume of solid matter, the total volume of the finished sample V b V is the volume of the solid substance t and pore volume V a The sum of , D is the sample diameter / cm, t is the sample thickness / cm, m is the sample mass, ρ t is the true density of quartz g / cm 3 .

[0044] Example 1

[0045] A method for testing the porosity of a high-purity quartz coating, the method comprising the following steps:

[0046] (1) Use 50-200 mesh high-purity quartz sand and a certain amount of pure water, add them into a ball mill, and ball mill for 12-15 hours to obtain a high-purity quartz slurry with a moisture content of 30%-40%.

[0047] (2) Cut a square crucible block of 160 mm × 160 mm from the crucible body to make a square mold base of 160 mm × 160 mm.

[0048] (3) Use the high-purity brushing method to moisturize the surface of the square 160mm×160mm mold base, and brush high-purity quartz slurry on the side wall of the mold base. Let the high-purity quartz slurry solidify on the side wall of the mold base to test whether the high-purity quartz slurry meets the requirements of high-purity quartz coating.

[0049] (4) Place a silicone mold with a diameter of 42 mm and a thickness of 2 mm on the mold base, take 5-6 g of high-purity quartz slurry and pour it into the circular mold cavity of the silicone mold. Let it stand for 3 hours to allow the high-purity quartz slurry to solidify, and then demold the solidified quartz slurry sample to obtain a circular primary embryo sample.

[0050] (5) Place the round embryonic sample in an oven at 105° and dry for 2 hours to obtain a round finished sample.

[0051] (6) Measure the weight, diameter and thickness of the circular finished sample, calculate the solid matter volume and pore volume of the circular finished sample based on the weight, diameter and thickness of the circular finished sample, and substitute the solid matter volume and pore volume of the circular finished sample into the porosity calculation formula to calculate the porosity of the circular finished sample to be 1.

[0052] (7) The round finished product sample was sintered at 1135 degrees for 3 hours, and the measured porosity was 2 according to the standard GB / T 2997-2015 test method for bulk density, apparent porosity and true porosity of dense shaped refractory products.

[0053] (8) Compare porosity 1 and porosity 2 to obtain the deviation value of porosity 1 and porosity 2. According to the deviation value of porosity 1 and porosity 2, verify whether the porosity test method is feasible and confirm that the porosity test result is accurate.

[0054] The following is the comparative experimental data of porosity 1 and porosity 2 of high-purity quartz samples produced by the same mold:

[0055]

[0056]

[0057] The test results of the samples are shown in Table 1. The average value of porosity 1 is 29.92%, the average value of porosity 2 is 29.28%, and the deviation between the two is 2.21%. The deviation value is less than 5%, that is, the test method is feasible and the test results are accurate.

[0058] Example 2

[0059] A method for testing the porosity of a high-purity quartz coating, the method comprising the following steps:

[0060] (1) Use 50-200 mesh quartz sand and a certain amount of pure water, add them into a ball mill, and ball mill for 12-15 hours to obtain a quartz sand slurry with a moisture content of 30%-40%. Add a certain amount of 200-400 mesh and 100-200 mesh quartz sand, stir the mixture for 1-3 minutes, and obtain a high-purity quartz slurry with a moisture content of 20%-30%.

[0061] (2) Cut a square crucible block of 160 mm × 160 mm from the crucible body to make a square mold base of 160 mm × 160 mm.

[0062] (3) Use the high-purity brushing method to moisturize the surface of the square 160mm×160mm mold base, and brush high-purity quartz slurry on the side wall of the mold base. Let the high-purity quartz slurry solidify on the side wall of the mold base to test whether the high-purity quartz slurry meets the requirements of high-purity quartz coating.

[0063] (4) Place a silicone mold with a diameter of 42 mm and a thickness of 2 mm on the mold base, take 7-8 g of high-purity quartz slurry and pour it into the circular mold cavity of the silicone mold. Let it stand for 2 hours to allow the high-purity quartz slurry to solidify, and then demold the solidified quartz slurry sample to obtain a circular primary embryo sample.

[0064] (5) Place the round embryonic sample in an oven at 110° and dry for 2 hours to obtain a round finished sample.

[0065] (6) Measure the weight, diameter and thickness of the circular finished sample, calculate the solid matter volume and pore volume of the circular finished sample based on the weight, diameter and thickness of the circular finished sample, and substitute the solid matter volume and pore volume of the circular finished sample into the porosity calculation formula to calculate the porosity of the circular finished sample to be 1.

[0066] (7) The round finished product sample was sintered at 1135 degrees for 3 hours, and the measured porosity was 2 according to the standard GB / T 2997-2015 test method for bulk density, apparent porosity and true porosity of dense shaped refractory products.

[0067] (8) Compare porosity 1 and porosity 2 to obtain the deviation value of porosity 1 and porosity 2. According to the deviation value of porosity 1 and porosity 2, verify whether the porosity test method is feasible and confirm that the porosity test result is accurate.

[0068] The following is the comparative experimental data of porosity 1 and porosity 2 of high-purity quartz samples produced by the same mold:

[0069]

[0070] The average value of porosity 1 is 19.59%, and the average value of porosity 2 is 19.25%. The deviation between the two is 1.76%, and the deviation value is less than 5%, which means that the test method is feasible and the test results are accurate.

[0071] Example 3

[0072] A method for testing the porosity of a high-purity quartz coating, the method comprising the following steps:

[0073] (1) Use 50-200 mesh quartz sand and a certain amount of pure water, add them into a ball mill, and ball mill for 12-15 hours to obtain a quartz sand slurry with a moisture content of 30%-40%. Add a certain amount of 200-400 mesh and 50-200 mesh quartz sand, stir the mixture for 1-3 minutes, and obtain a high-purity quartz slurry with a moisture content of 20%-30%.

[0074] (2) Cut a square crucible block of 160 mm × 160 mm from the crucible body to make a square mold base of 160 mm × 160 mm.

[0075] (3) Use the high-purity brushing method to moisturize the surface of the square 160mm×160mm mold base, and brush high-purity quartz slurry on the side wall of the mold base. Let the high-purity quartz slurry solidify on the side wall of the mold base to test whether the high-purity quartz slurry meets the requirements of high-purity quartz coating.

[0076] (4) Place a silicone mold with a diameter of 42 mm and a thickness of 2 mm on a mold base, take 8-9 g of high-purity quartz slurry and pour it into the circular mold cavity of the silicone mold. Let it stand for 2 h to allow the high-purity quartz slurry to solidify, and then demold the solidified quartz slurry sample to obtain a circular primary embryo sample.

[0077] (5) Place the round embryonic sample in an oven at 115° and dry for 2 hours to obtain a round finished sample.

[0078] (6) Measure the weight, diameter and thickness of the circular finished sample, calculate the solid matter volume and pore volume of the circular finished sample based on the weight, diameter and thickness of the circular finished sample, and substitute the solid matter volume and pore volume of the circular finished sample into the porosity calculation formula to calculate the porosity of the circular finished sample to be 1.

[0079] (7) The round finished product sample was sintered at 1135 degrees for 3 hours, and the measured porosity was 2 according to the standard GB / T 2997-2015 test method for bulk density, apparent porosity and true porosity of dense shaped refractory products.

[0080] (8) Compare porosity 1 and porosity 2 to obtain the deviation value of porosity 1 and porosity 2. According to the deviation value of porosity 1 and porosity 2, verify whether the porosity test method is feasible and confirm that the porosity test result is accurate.

[0081] The following is the comparative experimental data of porosity 1 and porosity 2 of high-purity quartz samples produced by the same mold:

[0082]

[0083] The average value of porosity 1 is 18.78%, and the average value of porosity 2 is 18.33%. The deviation between the two is 2.47%, and the deviation value is less than 5%, which means that the test method is feasible and the test results are accurate.

[0084] The working principle of the present invention is: the test method for the porosity of the high-purity quartz coating proposed in the present application can use the same high-purity quartz slurry as the high-purity quartz coating to make a sample block, and measure the weight, diameter and thickness of the sample block, and calculate the solid matter volume and pore volume of the finished sample block according to the weight, diameter and thickness of the sample block, and then calculate the porosity of the sample block according to the solid matter volume and pore volume of the sample block, so as to know the porosity of the high-purity quartz coating, optimize the test process, reduce the difficulty of the test operation, avoid the need to sinter the sample block according to the standard test method before testing the porosity of the sample block, reduce energy waste, save time and effort, and improve the testing efficiency and sustainability of the coating porosity.

[0085] In addition, in order to ensure the accuracy of the test results, the samples were sintered according to the standard GB / T 2997-2015 test method for bulk density, apparent porosity and true porosity of dense shaped refractory products, and the porosity of the sintered samples was calculated. The two porosities before and after sintering were compared to obtain the deviation value between the two porosities. The feasibility of this test method was verified based on the deviation value and deviation range between the porosities calculated by the two methods, thereby confirming that the porosity test results are accurate and ensuring the accuracy of the test results.

[0086] What is described above is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A method for testing the porosity of a high-purity quartz coating, characterized in that: The method comprises the following steps: Step 1: Select high-purity quartz sand and pure water, grind the high-purity quartz sand, and mix the grinded high-purity quartz sand with pure water to obtain high-purity quartz slurry; Step 2: Cut a crucible block from the crucible body to make a mold base; Step 3: Use a high-purity brushing method to replenish water on the surface of the mold base, and brush high-purity quartz slurry on the side wall of the mold base, let the high-purity quartz slurry solidify on the side wall of the mold base, and test whether the high-purity quartz slurry meets the requirements of high-purity quartz coating; Step 4: placing the shaping mold on the end face of the mold base, pouring high-purity quartz slurry into the mold cavity of the shaping mold, allowing the high-purity quartz slurry to stand, allowing the high-purity quartz slurry to solidify, and demolding the solidified quartz slurry sample to obtain a primary embryo sample; Step 5: Place the pre-embedded sample block in an oven for drying to obtain a finished sample block; Step 6, measuring the weight, diameter and thickness of the finished sample obtained in step 5, calculating the solid matter volume and pore volume of the finished sample according to the weight, diameter and thickness of the finished sample, and substituting the solid matter volume and pore volume of the finished sample into the porosity calculation formula to calculate the porosity 1 of the finished sample; Step 7: high temperature sintering the finished sample obtained in step 5 to obtain a final sample, and calculating the porosity of the final sample according to the standard GB / T 2997-2015 test method for bulk density, apparent porosity and true porosity of dense shaped refractory products to obtain a porosity of 2; Step 8: Compare the porosity 1 obtained in step 6 with the porosity 2 obtained in step 7 to obtain the deviation value of the porosity 1 and the porosity 2. According to the deviation value of the porosity 1 and the porosity 2, verify whether the porosity test method is feasible and confirm that the porosity test result is accurate. The porosity calculation steps of the finished product sample in step 6 are as follows: (1) (2)V a =V b -V t (3) (4) Substituting formula (1), (2) and (3) into formula (4) yields the calculation formula for the porosity of the finished sample: (5) Where π a is the porosity of the finished sample, V b is the total volume of the finished sample, V a is the pore volume, V t is the volume of solid matter, the total volume of the finished sample V b V is the volume of the solid substance t and pore volume V a The sum of , D is the sample diameter / cm, t is the sample thickness / cm, m is the sample mass, ρ t is the true density of quartz g / cm 3 .

2. A method for testing the porosity of a high-purity quartz coating according to claim 1, characterized in that: The grinding and mixing equipment for the high-purity quartz sand in step 1 is a ball mill, and the ball milling time is 12-15 hours.

3. The method for testing the porosity of a high-purity quartz coating according to claim 1, characterized in that: The water content of the high-purity quartz slurry in step 1 is 20%-40%.

4. The method for testing the porosity of a high-purity quartz coating according to claim 1, characterized in that: The shaping mold in step 4 is a silicone mold, and the mold cavity shape in the silicone mold is circular.

5. The method for testing the porosity of a high-purity quartz coating according to claim 1, characterized in that: In the step 2, the end surface area of ​​the mold base is larger than the area of ​​the shaping mold.

6. A method for testing the porosity of a high-purity quartz coating according to claim 1, characterized in that: The standing time of the high-purity quartz slurry in step 4 is 1-3 hours.

7. A method for testing the porosity of a high-purity quartz coating according to claim 1, characterized in that: The drying temperature of the primary embryo sample in step 5 is 105-115°, and the drying time is 2-3 hours.

8. The method for testing the porosity of a high-purity quartz coating according to claim 1, characterized in that: The weight, diameter and thickness of the finished product sample in step 6 are measured using an electronic scale and a vernier caliper.

9. A method for testing the porosity of a high-purity quartz coating according to claim 1, characterized in that: The deviation value range of porosity 1 and porosity 2 in step eight is 0-5%.

10. A method for testing the porosity of a high-purity quartz coating according to claim 1, characterized in that: The sintering temperature of the finished sample in step seven is 1100-1200°, and the sintering time is 2-4h.